RealWorld programming with PHP 5 - Fontana, John.; Safari eBooks ([S.l.] : Virtual Training Co., 2011)
"PHP has become the most popular serverside programming language for building web applications and is currently in use on more than 75% of all web servers. As of the release of PHP5, it has matured into a sophisticated language with advanced objectoriented capabilities. This course will take you through the basics of PHP, all the way through to its most advanced features. Author John Fontana demonstrates practical knowledge that can be applied to everyday programming tasks in the real world."--Resource description page.
Title from resource description page (viewed Feb. 7, 2013).
Presenter: John Fontana.
Keywords: PHP (Computer program language) -- Handbooks, manuals, etc; Web sites -- Design -- Handbooks, manuals, etc; Electronic books